Advanced fitness assessment and exercise prescription - Heyward, Vivian H; Gibson, Ann L (Human Kinetics, 2014)
A text that intends to bridge the gap between research and practice and synthesizes concepts and theories from exercise physiology, kinesiology, measurement, psychology and nutrition to provide a clearly defined approach to physical fitness testing and the design of individualised exercise programmes